2022
DOI: 10.1002/anie.202203843
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy to Fight Metallodrug Resistance: Mitochondria‐Relevant Treatment through Mitophagy to Inhibit Metabolic Adaptations of Cancer Cells

Abstract: Metabolic adaptations can help cancer cells to escape from chemotherapeutics, mainly involving autophagy and ATP production. Herein, we report a new rhein‐based cyclometalated IrIII complex, Ir‐Rhein, that can accurately target mitochondria and effectively inhibit metabolic adaptations. The complex Ir‐Rhein induces severe mitochondrial damage and initiates mitophagy to reduce the number of mitochondria and subsequently inhibit both mitochondrial and glycolytic bioenergetics, which eventually leads to ATP starv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Studies have shown that ROS generated by PDT could induce autophagy in addition to apoptosis. Besides, RES triggers the deficiency of ATP by inhibiting the oxygen consumption of tumor cells, which further induces autophagy. , Therefore, we further examined the level of autophagy in this photodynamic therapy combined with RES.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that ROS generated by PDT could induce autophagy in addition to apoptosis. Besides, RES triggers the deficiency of ATP by inhibiting the oxygen consumption of tumor cells, which further induces autophagy. , Therefore, we further examined the level of autophagy in this photodynamic therapy combined with RES.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolism can help cancer cells escape chemotherapy, and this process mainly involves autophagy and ATP production. In view of this, Wang et al reported a new ring metallized Ir (III) complex (Ir-Rhein) based on rhein, which can accurately target mitochondria and effectively inhibit metabolic adaptation 184 . The Ir-Rhein complex can cause serious mitochondrial damage, lead to mitophagy and reduce the number of mitochondria, and then restrict the biological energy of mitochondria and glycolysis, eventually resulting in ATP starvation and death.…”
Section: Small Molecules Pharmacological Regulation Of Mitophagymentioning
confidence: 99%
“…The Ir-Rhein complex can cause serious mitochondrial damage, lead to mitophagy and reduce the number of mitochondria, and then restrict the biological energy of mitochondria and glycolysis, eventually resulting in ATP starvation and death. Studies have shown that Ir-Rhein can overcome the resistance of cancer cells to cisplatin, developing a new mitochondrial-related therapy to overcome resistance to metal drugs 184 .…”
Section: Small Molecules Pharmacological Regulation Of Mitophagymentioning
confidence: 99%
“…Compound 49 can induce mitochondria-mediated cell death in A549cisR cells under 405 nm radiation, thereby overcoming drug resistance (Table 1). Based on compound 45, Wang et al synthesized a Rhein-modified cyclometallated Ir(III) compound 51 (Figure 4), which could precisely target mitochondria, induce severe mitochondrial damage and inhibit glycolytic bioenergetics, ultimately leading to death from ATP starvation (Table 1) (Wang et al, 2022). In addition, compound 51 can also regulate the cisplatin metabolic pathway in A549cisR cells, such as up regulating the inflow of CTR1 and down regulating the outflow of MRP2 transporter, thereby producing good anti proliferation performance against cisplatin resistant cancer cells.…”
Section: Cyclometalated Iridium (Iii) Complexesmentioning
confidence: 99%